2013
DOI: 10.1310/tsr2001-78
|View full text |Cite
|
Sign up to set email alerts
|

Altered Taste and Stroke: A Case Report and Literature Review

Abstract: Patients with altered taste perception following stroke are at risk for malnutrition and associated complications that may impede recovery and adversely affect quality of life. Such deficits often induce and exacerbate depressive symptomatology, which can further hamper recovery. It is important for clinicians and rehabilitation specialists to monitor stroke patients for altered taste perception so that this issue can be addressed. The authors present the case of a patient who experienced an isolated ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Hyperhomocysteinemia was prevalent in about 20% of the patients with a history of stroke [ 5 ]. Malnutrition which is common in stroke patients [ 6 7 ] has been reported to be associated with high Hcy levels [ 8 ]. Low dietary vitamin intake was also reported to be a risk factor for high Hcy levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhomocysteinemia was prevalent in about 20% of the patients with a history of stroke [ 5 ]. Malnutrition which is common in stroke patients [ 6 7 ] has been reported to be associated with high Hcy levels [ 8 ]. Low dietary vitamin intake was also reported to be a risk factor for high Hcy levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the gustatory pathway is not yet fully elucidated. Multiple lesion locations were related to ageusia, foremost the insular cortex [ 6 , 7 , 8 , 9 , 10 ], the pons [ 5 , 11 , 12 ], and the thalamus [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several diverse taste alterations were reported with left insular infarct [ 6 , 7 , 8 ] and right-sided insular lesions [ 8 , 9 , 10 ]. A patient suffered changes for salty and sour taste recognition with normal recognition for bitter and sweet following stroke of the left insular cortex [ 6 ], while in another patient the same lesion location resulted in a diminished pleasure in taste and persistent taste of rotten melon [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that surgical interventions in the head and neck area can lead to reports of taste defects and weight loss (Caldas et al 2013; Woschnagg et al 2002). Several studies have suggested that stroke patients with damage to area associated with gustatory functioning report taste abnormalities and have weight regulation problems (Dutta et al 2013; Finsterer et al 2004; Green et al 2008; Heckmann et al 2005). A significant fraction of cancer patients have altered taste perception and exhibit both decreased food intake and weight loss (Baharvand et al 2013; Boltong and Keast 2012; Cohen et al 2014; Comeau et al 2001; Epstein and Barasch 2010; Hutton et al 2007; Mahmoud et al 2011; Mattsson et al 1992; Peregrin 2006; Sánchez-Lara et al 2010).…”
Section: Taste Food Intake/preference and Metabolic Diseasementioning
confidence: 99%